Dynamics of Nonplanar Thrust Faults Governed by Various Friction Laws. Issue 6 (27th June 2018) - Luo, Bin; Duan, Benchun
Abstract: Large‐scale irregular geometry of a fault surface, such as seamounts and subducted oceanic plateaus, is a prevailing factor that introduces stress heterogeneity and affects rupture dynamics. However, dynamic ruptures are also controlled by the constitutive laws that describe how fault friction evolves. In this study, we explicitly incorporate nonplanar thrust fault geometry into a three‐dimensional finite element model to numerically simulate spontaneous dynamic rupture and explore how dynamic ruptures would behave on a nonplanar fault surface under the influence of different friction laws. Our results show that a subducted oceanic relief (a bump) could act as a rupture barrier with its high strength area being unfavorable for rupture propagation, and such a geometrical effect varies with the dimension of a bump. When a bump is too high, the dynamic rupture is completely arrested. When the bump is too low, the rupture is barely affected. When the bump is of an intermediate height, the rupture is obstructed by the bump and splits into two parts, which circumvent the high strength area of the bump and then converge on the other side, triggering a strong slip velocity pulse. The relation between these rupture behaviors and bump geometry under a given prestress condition varies with the specific forms of friction law, which determines how fast a rupture releases energy and how strong a bump can be as a barrier. Key Points: Friction laws can play an important role in dynamic rupture propagation of nonplanar faults The slip‐weakening law and rate‐ and state‐dependent laws lead to different yield strength on a bump geometry The relation between rupture behavior and bump geometry under a given prestress condition varies with the specific forms of friction law